The Effect of Frog Jump Training on the Smash Ability of Junior Volleyball Players from North Bengkulu 08 - Fitrah Ramdani; Deffri Anggara; Megi Personi (UNIVED Press, Universitas Dehasen Bengkulu, 2026)
This study aimed to determine the effect of frog jump training on the smash ability of Junior 08 North Bengkulu volleyball athletes. A total sampling technique was employed, involving 15 volleyball athletes who were members of the Junior 08 North Bengkulu Volleyball Team. This experimental study used a One Group Pretest–Posttest Design, which is a pre-experimental design involving a pretest (test conducted before the treatment) and a posttest (test conducted after the treatment) within a single group. Data were collected using test scores. The data were analyzed using descriptive statistical techniques and the t-test. The results of the study indicated that frog jump training had a significant effect on the smash ability of Junior 08 North Bengkulu volleyball athletes. The calculated t-value was 3.163, while the t-table value was 2.145 at a significance level of α = 0.05 and df = 15.